M1 macrophage exosomes engineered to foster M1 polarization and target the IL-4 receptor inhibit tumor growth by reprogramming tumor-associated macrophages into M1-like macrophages. (November 2021) - Gunassekaran, Gowri Rangaswamy; Poongkavithai Vadevoo, Sri Murugan; Baek, Moon-Chang; Lee, Byungheon
Abstract: M2-polarized, pro-tumoral tumor-associated macrophages (TAMs) express the interleukin-4 receptor (IL4R) at higher levels compared with M1-polarized, anti-tumoral macrophages. In this study, we harnessed M1 macrophage-derived exosomes engineered to foster M1 polarization and target IL4R for the inhibition of tumor growth by reprogramming TAMs into M1-like macrophages. M1 exosomes were transfected with NF-κB p50 siRNA and miR-511–3p to enhance M1 polarization and were surface-modified with IL4RPep-1, an IL4R-binding peptide, to target the IL4 receptor of TAMs (named IL4R-Exo(si/mi). IL4R-Exo(si/mi) were internalized and downregulated target gens in M2 macrophages and decreased M2 markers, while increasing M1 markers, more efficiently compared with untargeted and control peptide-labeled exosomes and exosomes from non-immune, normal cells. Whole-body fluorescence imaging showed that IL4R-Exo(si/mi) homed to tumors at higher levels compared with the liver, unlike untargeted and control peptide-labeled exosomes. Systemic administration of IL4R-Exo(si/mi) inhibited tumor growth, downregulated target genes, and decreased the levels of M2 cytokines and immune-suppressive cells, while increasing the levels of M1 cytokines and immune-stimulatory cells, more efficiently than untargeted and control peptide-labeled exosomes. These results suggest that IL4R-Exo(si/mi) inhibits tumor growth by reprogramming TAMs into M1-like macrophages and increasing anti-tumor immunity, thus representing a novel cancer immunotherapy.